Challenges for Elementary School Teachers in Attitude Assessment during Online Learning - Fauzani, Ratna Ainun; Senen, Anwar; Retnawati, Heri (Journal of Education Research and Evaluation, 2021)
This study aims to describe the various challenges faced by teachers in assessing attitudes through online learning in elementary schools during Covid-19. This study used a qualitative method with a type of phenomenology. The data collection was carried out through interviews and focus group discussion (FGD) through Google Meet and WhatsApp and open questionnaires via Google Form. The technique in analyzing the data was finding specific themes and looking for the relationships between them to achieve a proper understanding. The results show that the challenges in assessing attitudes faced by the teacher included six themes, namely understanding, planning, implementing, and reflecting on attitude assessment, the condition of parents and students, and mastery of media and learning tools. These various challenges showed advices and recommendations for schools and policymakers to improve the quality in teaching practices.Â